2002
DOI: 10.1111/1467-7679.00162
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technologies for Direct Poverty Alleviation: Costs and Benefits

Abstract: Information and communications technologies (ICTs) are powerful tools for empowerment and income generation in developing countries. The costeffectiveness of different ICTs does vary between developed and less developed countries, however. This article reviews the potential efficacy of radio, telephony and the Internet as tools of direct poverty alleviation in the latter. While the requirements for their successful utilisation make radio and telephone far more suitable technologies for the poor, traditional IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 13 publications
(10 reference statements)
1
84
0
1
Order By: Relevance
“…Language remains a significant barrier to use, as is suggested by a study in Slovenia, which found that 75% of those who were fluent in English used the Internet compared to only 1% of non-English speakers (Kenny, 2002). found that countries where English is the official or most widely spoken language have significantly higher Internet users per capita.…”
Section: The Internet In Ldcsmentioning
confidence: 94%
See 2 more Smart Citations
“…Language remains a significant barrier to use, as is suggested by a study in Slovenia, which found that 75% of those who were fluent in English used the Internet compared to only 1% of non-English speakers (Kenny, 2002). found that countries where English is the official or most widely spoken language have significantly higher Internet users per capita.…”
Section: The Internet In Ldcsmentioning
confidence: 94%
“…It is more expensive to provide networked services such as electricity and telecommunications to rural areas because the infrastructure required per customer is higher than in urban areas. The physical costs of computer and telephone access are unlikely to drop below US$1000 even in relatively population-dense rural areas with electricity access (Kenny, 2002). In lowdensity areas without networked services, costs of Internet infrastructure can rise as high as US$20 000 per computer.…”
Section: The Internet In Ldcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information and communication technologies are powerful tools for empowerment in developing countries (Kenny, 2002). Transportation means such as a car or a bicycle, and means of communication are necessary to improve people's livelihoods.…”
Section: Social Conditionsmentioning
confidence: 99%
“…Entretanto, a verdade é que a maioria da humanidade fica excluída dessa rede global de integração física e semiótica. Dentro do sistema-mundo, as estruturas de inteligência coletiva se misturam perigosamente com a concentração de poder, o individualismo, o consumismo e a alienação, criando um território excludente e ameaçador (LÉVY, 1994b;KENNY, 2002;MERLE, 2005;GURSTEIN, 2007). Aqueles estranhos à sua hermenêutica, que é a hermenêutica do Ocidente, ficam marginalizados.…”
Section: Refletir Sobre a Ontologia Das Redes Na América Latinaunclassified